ESTIMATING OF OKUN’S RELATIONSHIP IN IRAQI AGRICULTURAL SECTOR FOR THE PERIOD 1998-2019 USING BOOTSTRAP ARDL METHODOLOGY - Al-Badawi, S. A.; R. T. Al-Wasity (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to test the relationship between the unemployment rate and agricultural growth rates in the agricultural sector of Iraq according to Okun’s Law for the period 1998-2019. The differences and gap versions of Okun’s Law for the relationship was conducted, Alongside with Hodrick-Prescott (HP) filter to find the potential production and the Baxter-King (BK) filter to find the trend of unemployment for the agricultural sector, and then to find production and unemployment gaps. Bootstrapping method was used to generate data because the lack of data and Augmented ARDL to identify the cointegration. The result of independent-F test at the level was insignificant with a value of 1.49 for the differences model, that is less than the critical value which is 9.26 of the 0.05 level of significance. While the result of independent-F test at the level of the gap model was 1.89, which is less than the critical value which is 12.8 at 0.05 the level of significance. Thus, confirming the absence of a co-integration relationship between the two variables. This result confirms the complete absence of Okun’s relationship with the two versions in the Iraqi agricultural sector.